Short-term variation of chemical property of water and microplankton community in the coastal area near Syowa Station, Antarctica, in midsummer of 1984, I. Chemical property including chlorophyll a - Iwanami, Keisuke; Futatsumachi, Satoru; Taniguchi, Akira (1986)
P(論文) Variation of chemical porperties and chlorophyll α standing stock in the water column below fast ice were monitored in the coastal area north of Syowa Station, Antarctica, for 2 weeks in midsummer of 1984. Because the ice was continuously melting, the surface water was diluted to a greater extent and isolated from underlying waters by a well-defined pycnocline. Nitrate and nitrite were rapidly and completely depleted from the surface water. Silicate was also removed rapidly but remained at a certain level in the latter half of the investigation period. Phosphate and ammonium were apparently replenished probably by excretion of larger animals such as seals. Despite of not a small amount of the nutrients, chlorophyll α decreased in the surface water. Excess dilution with ice melted water is likely to be detrimental to most phytoplankters. During these variations in the surface layer, the chlorophyll maximum was formed in the subsurface layer and clearly observed to become definite at shallower depths. The present findings demonstrate that the variations of phytoplankton stocks as well as environmental conditions within a limited period can be very intensive in midsummer. departmental bulletin paper